STRENGTH TRAINING AND RESISTANCE TRAINING ON FUNCTIONAL FUNCTIONAL CAPACITY AND QUALITY OF LIFE OF ELDERLY PHYSICALLY INDEPENDENT (Fiep Bulletin - online, 2011)
The aim of this study was to analyze the effects of eight weeks of training by two protocols, entitled Training Force(TF) and Resistive Functional Training(FFT), in relation to functional capacity and quality of life of elderly physically independent. For the research in question was used as a criterion for sampling the simple random probabilistic manner. The sample consisted of 30 elderly male and female, minimum age of 60 years, divided into three groups: Group Strength Training(GTF=10), group of Functional Training Resistive (GTFR=10) and a control group(GC=10). For the assessment of functional capacity was applied to the Protocol Development Group for Latin American Maturity(GDLAM). To measure the benefits related to quality of life we used the Quality of Life Questionnaire SF-36.The data were treated statistically by the SPSS 16.0, which was adopted frequency distribution for qualitative data, descriptive statistics for quantitative data, the Student t test to compare differences before and after training in each group and analysis variance of a criterion for comparison between groups. The study acknowledged a p The aim of this study was to analyze the effects of eight weeks of training by two protocols, entitled Training Force(TF) and Resistive Functional Training(FFT), in relation to functional capacity and quality of life of elderly physically independent. For the research in question was used as a criterion for sampling the simple random probabilistic manner. The sample consisted of 30 elderly male and female, minimum age of 60 years, divided into three groups: Group Strength Training(GTF=10), group of Functional Training Resistive (GTFR=10) and a control group(GC=10). For the assessment of functional capacity was applied to the Protocol Development Group for Latin American Maturity(GDLAM). To measure the benefits related to quality of life we used the Quality of Life Questionnaire SF-36.The data were treated statistically by the SPSS 16.0, which was adopted frequency distribution for qualitative data, descriptive statistics for quantitative data, the Student t test to compare differences before and after training in each group and analysis variance of a criterion for comparison between groups. The study acknowledged a p≤0.05 for statistical significance. Overall, the results indicated improvement in functional capacity of the experimental groups(GTFandGTFR). The control group showed deterioration in functional capacity compared to the experimental groups. Qualitative analysis showed that the experimental groups showed improvement in the control group.
Keywords: functional capacity; strength training and functional training resisted